1998
DOI: 10.1111/j.1095-8649.1998.tb01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐induced changes of survival, development and yolk partitioning in Chondrostoma nasus

Abstract: Fertilized Chondrostoma nasus eggs were incubated at 10, 13, 16 and 19 C until full resorption of the yolk sac. High survival was observed at 10-16 C (89-92% at the onset of external feeding), whereas at 19 C survival was depressed (76%). The time at which 5, 50 and 95% of individuals had hatched, filled the swim bladder, ingested the first food and fully resorbed the yolk sac was determined. An increase in temperature accelerated development and made it more synchronous. Within the period from fertilization t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
107
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(120 citation statements)
references
References 36 publications
7
107
1
3
Order By: Relevance
“…Herzig and Winkler (1986) established an equation linking the period of incubation (D in days, 50% of hatches) to temperature (T in°C): D = 1258/(T -2.62) 1.994 or, 23.1 days at 10°C and 5.8 days at 17°C, the range of validity of the equation. For the larvae, the optimum temperature lies between 15°C (Kamler et al, 1998;Penáz, 1974ain Schiemer et al, 2003 on the Danube) and 25°C (Keckeis et al, 2001;Schiemer et al, 2004). The maximum tolerated is on the order of 28°C (Penáz, 1974ain Schiemer et al, 2003 on the Danube; Schiemer et al, 2003;Spurny et al, 2004 in Wolnicki andGorni, 1994), a datum found in two articles (Wolnicki and Gorni, 1994;Schiemer et al, 2003).…”
Section: Nase (Chondrostoma Nasus)mentioning
confidence: 91%
See 2 more Smart Citations
“…Herzig and Winkler (1986) established an equation linking the period of incubation (D in days, 50% of hatches) to temperature (T in°C): D = 1258/(T -2.62) 1.994 or, 23.1 days at 10°C and 5.8 days at 17°C, the range of validity of the equation. For the larvae, the optimum temperature lies between 15°C (Kamler et al, 1998;Penáz, 1974ain Schiemer et al, 2003 on the Danube) and 25°C (Keckeis et al, 2001;Schiemer et al, 2004). The maximum tolerated is on the order of 28°C (Penáz, 1974ain Schiemer et al, 2003 on the Danube; Schiemer et al, 2003;Spurny et al, 2004 in Wolnicki andGorni, 1994), a datum found in two articles (Wolnicki and Gorni, 1994;Schiemer et al, 2003).…”
Section: Nase (Chondrostoma Nasus)mentioning
confidence: 91%
“…In view of fishing results on the Rhône, Ginot et al (1996) establish optimum temperatures for nase juveniles between 7°C and 27°C. It seems more realistic to put these temperatures within a more limited range, comparable to that for the embryo, between 15°C and 25°C (Kamler et al, 1998;Penáz, 1974bin Schiemer et al, 2003Teletchea et al, 2009b). Bruslé and Quignard (2001) are the only authors to define thermal tolerance thresholds for the adult: they consider that the range of temperatures within which the adult feeds is between 4°C and 24°C.…”
Section: Nase (Chondrostoma Nasus)mentioning
confidence: 99%
See 1 more Smart Citation
“…At other temperatures, the individuals that left the egg membranes usually show less advanced ontogenic development (Kokurewicz 1969(Kokurewicz , 1970Kupren et al 2011). The reason for faster hatching of embryos at higher temperatures is their increased mobility in warmer water and earlier excretion of the hatching enzyme (Blaxter 1969(Blaxter , 1992Kamler 1992;Kamler et al 1998;Korwin-Kossakowski 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Adults undertake spawning migrations into smaller tributaries or to gravel bars with swift currents for up to several dozen kilometres (Keckeis et al 1996;Peň áz 1996). After the period of yolk-sac depletion during which larvae exhibit a benthic life style (usually 4 to 7 dph; Keckeis et al 1996;Kamler et al 1998), larvae and early juveniles commonly disperse downstream from spawning sites to low-flowing inshore areas where they feed on small invertebrates (Kamler and Keckeis 2000;Reichard et al 2001).…”
Section: Model Organismmentioning
confidence: 99%